Holocene coastal environmental changes inferred by multi-proxy analysis from Lago Formoso sediments in Maranhão State, northeastern Brazil - Caio Alves de Moraes; Marcondes Lima da Costa; Alexandre Guida Navarro; Maria Ecilene Nunes da Silva Meneses; Leonardo Boiadeiro Ayres Negrão; Herbert Pöllmann; Hermann Behling (PANGAEA, 2021)
The history of the coastal environment in the northern part of northeastern Brazil and the role of sea-level and climate change as well as the human impact during the past has been still little know. In order to shed more light on coastal ecosystem dynamics and its influencing factors, a 300 cm long sediment core has been taken using a Russian corer from Lago Formoso (3°15 extquotesingle14S / 45°23 extquotesingle10W; elevation of 10 meters above sea-level) located around 150 km distance from the present-day coast in Maranhão State. The fieldwork has been carried out during the dry season, with the sampling on the 10th of December 2018. The lake has an area of approximately 500 ha and is inserted into the coastal plains of Maranhão. During the rainy season (in May is the maximum) the lake is seasonally inundated with the highest water stand of up to 8 m, while during the dry season the shallow lake has a 1.3 m water depth. The core has been radiocarbon dated and analyzed by pollen, spores, charcoal, X-Ray Fluorescence (XRF), X-ray Powder Diffraction (XRPD), LOI, and sedimentary characteristics. The main aim of this work is to answer the specific research questions: 1) How were the dynamics of vegetation in the study area? 2) How sea-level and climate influenced the coastal environment since the mid-Holocene? 3) When occurred the Atlantic Ocean regression? 4) Since when and how strong did humans have influenced the environment in the region?